Stylistics Analysis of The Poem “An Old Man’s Winter Night” by Robert Frost: English - Saputra, Johanes Rhana; Nur Abida, Fithriyah Inda (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Stylistics analysis gives an impartial and scientific opinion based on solid quantifiable data and methodical application. It makes use of specific technical vocabulary and notions derived from linguistics. The four layers of language aspects that can be studied stylistically are phonology, graphology, grammar, and semantics. The purpose of this research is to examine the stylistic features of Robert Frost's poem "An Old Man’s Winter Night" through the lens of stylistic analysis. The structure and style of Robert Frost's writing, as well as his subjects, viewpoints, and themes are all examined in this study. Each level has been thoroughly investigated, with attention paid to the phonetic, phonological, graphitic, semantic, and grammatical aspects of language choice. This research is descriptive qualitative with content analysis approach. To attain the purpose, the data is analysed through stylistics devices. Frost employed a variety of stylistic elements to emphasize his point, including alliteration, assonance, tone modulation, denotation, connotation, metaphor, personification, symbolism, and imagery.